Magnetic Resonance Elastography of Liver in Light Chain Amyloidosis - Venkatesh, Sudhakar K. (J Clin Med, 2019)
In this paper, we present our preliminary findings regarding magnetic resonance elastography (MRE) on the livers of 10 patients with systemic amyloidosis. Mean liver stiffness measurements (LSM) and spleen stiffness measurements (SSM) were obtained. Magnetic resonance imaging (MRI) images were analyzed for the distribution pattern of amyloid deposition. Pearson correlation analysis was performed in order to study the correlation between LSM, SSM, liver span, liver volume, spleen span, spleen volume, serum alkaline phosphatase (ALP), N-terminal pro b-type natriuretic peptide (NT pro BNP), and the kappa and lambda free light chains. An increase in mean LSM was seen in all patients. Pearson correlation analysis showed a statistically significant correlation between LSM and liver volume (r = 0.78, p = 0.007) and kappa chain level (r = 0.65, p = 0.04). Interestingly, LSM did not correlate significantly with SSM (r = 0.45, p = 0.18), liver span (r = 0.57, p = 0.08), or serum ALP (r = 0.60, p = 0.07). However, LSM correlated significantly with serum ALP when corrected for liver volume (partial correlation, r = 0.71, p = 0.03) and NT pro BNP levels (partial correlation, r = 0.68, p = 0.04). MRI review revealed that amyloid deposition in the liver can be diffuse, lobar, or focal. MRE is useful for the evaluation of hepatic amyloidosis and shows increased stiffness in hepatic amyloidosis. MRE has the potential to be a non-invasive quantitative imaging marker for hepatic amyloidosis.